2019
DOI: 10.1177/1071181319631053
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Cue Combinations: A Possible Approach to Designing In-Vehicle Takeover Requests for Semi-autonomous Driving

Abstract: The rapid growth of autonomous vehicles is expected to improve roadway safety. However, certain levels of vehicle automation will still require drivers to ‘takeover’ during abnormal situations, which may lead to breakdowns in driver-vehicle interactions. To date, there is no agreement on how to best support drivers in accomplishing a takeover task. Therefore, the goal of this study was to investigate the effectiveness of multimodal alerts as a feasible approach. In particular, we examined the effects of uni-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A two-way repeated-measures ANOVA was conducted on the 4 obstacle types (tire, construction zone, rain and wind, deer) x 6 NASA-TLX un-weighted subscales (mental demand, physical demand, temporal demand, performance, effort, and frustration) (similar to Huang et al, 2019). There was a significant main effect of obstacle type (F(1, 15) = 28.967, p < .001, partial η 2 = 0.659) and subscale (F(1, 15) = 10.325, p = .006, partial η 2 = 0.408) on workload (see Figure 4).…”
Section: Subjective Workloadmentioning
confidence: 99%
“…A two-way repeated-measures ANOVA was conducted on the 4 obstacle types (tire, construction zone, rain and wind, deer) x 6 NASA-TLX un-weighted subscales (mental demand, physical demand, temporal demand, performance, effort, and frustration) (similar to Huang et al, 2019). There was a significant main effect of obstacle type (F(1, 15) = 28.967, p < .001, partial η 2 = 0.659) and subscale (F(1, 15) = 10.325, p = .006, partial η 2 = 0.408) on workload (see Figure 4).…”
Section: Subjective Workloadmentioning
confidence: 99%
“…Clark and Feng [56] report lower TOTs for the young group for a TOT budget of 4.5s, and lower TOTs for the old group for a 7.5s TOT budget. TOR modality: Petermeijer et al [57] and Huang et al [58] compare different modalities for issuing the TOR. Auditory and tactile TORs are considered in [57] while auditory, tactile and visual TORs and their combinations are considered in [58].…”
Section: B Take-over Time Analysis In Autonomous Drivingmentioning
confidence: 99%
“…TOR modality: Petermeijer et al [57] and Huang et al [58] compare different modalities for issuing the TOR. Auditory and tactile TORs are considered in [57] while auditory, tactile and visual TORs and their combinations are considered in [58]. Both studies report the lowest TOTs for multimodal TORs.…”
Section: B Take-over Time Analysis In Autonomous Drivingmentioning
confidence: 99%
“…Although automated vehicles might be capable of sensing, collecting, integrating and processing a large volume of roadway condition information, as well as negotiating some operating situations, many domain experts still have doubts about safety. Research has indicated that such technologies can introduce additional safety risks, as the driver is disconnected from driving tasks and there may be vehicle conditions and road environments that are unmanageable by automation (Kockelman et al, 2016;Koopman & Wagner, 2017;ITF, 2018;Huang et al, 2019). Therefore, a driver may need to "takeover" vehicle control in certain hazard situations, including lost GPS signals, unclear and/or missing lane markings, construction zone entry points or road closures, and high traffic density (Körber, Prasch, & Bengler, 2018;Molnar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%